Assess whole-farm trade-offs and synergies for climate-smart agriculture - Mwongera, Caroline; Läderach, Peter R.D.; Acosta, Mariola; Ampaire, Edidah L.; Eitzinger, Anton; Lamanna, Christine; Mwungu, Chris Miyinzi; Shikuku, Kelvin Mashisia; Twyman, Jennifer; Winowiecki, Leigh Ann (International Center for Tropical Agriculture, 2017)
Research shows that climate-smart agriculture (CSA) is beneficial in increasing productivity, promoting resilience and reducing greenhouse gas emissions. Achieving benefits in all three dimensions is difficult, and so necessary choices among competing investments and objectives must be made. The complex nature of agricultural systems implies that there are always multiple outcomes and goals to choose from. Some are immediate whereas others are long term. Achieving some goals might compromise the ability to achieve others. To invest in and scale up successful interventions, evidence is needed to help select and assess benefits and limitations of different CSA interventions. Using this evidence to design portfolios of best-bet CSA options enables decision makers to identify and manage expectations, make informed choices and anticipate trade-offs.